SUSPECTED CLINICAL TOXOPLASMOSIS IN PET RABBITS (ORYCTOLAGUS CUNICULUS) IN LIMA, PERU - Lescano, Jesús; Quevedo, Miryam (Archives of Veterinary Science, 2018)
Toxoplasmosis is a prevalent disease among rabbits in many areas of the world. However, its clinical presentation is very uncommon. In South America, prevalence of toxoplasmosis in rabbits is unknown and clinical reports on this disease are scarce or inexistent. Antibodies against Toxoplasma gondii were found in four pet rabbits which were received at the XXXXX, XXXXX, XXXXX (Lima, Peru). These animals were received over about one year and belonged to different owners. The most common reasons for presentation were anorexia/hyporexia and difficulty to walk. The most frequently observed clinical sign was myalgia. All rabbits presented anemia, lymphopenia, and increased creatinine. The 75% (3/4) of patients died or were humanely euthanized. This article describes the presence of antibodies against T. gondii in clinically ill rabbits for the first time in Peru. Based on these observations, research on prevalence of toxoplasmosis in rabbits and its associated risk factors are recommended.